Prosedur Penerapan Dokumen Bill Of Lading Dalam Aktivitas Ekspor-Impor - FeviLia Dea Ayu; Ida Ayu Putu Widiati; I Wayan Arthanaya (Fakultas Hukum Universitas Warmadewa, 2020)
Abstract-The development and advancement of an industry in trade which is increasingly rapidly influencing the world economy, especially in international trade through exports and imports. The Bill of Lading in Indonesian is known as the